Teknologi Augmented Reality untuk instalasi kelistrikan gedung - Ari Sugiharto; Ikrima Alfi; Suwirno Suwirno (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2022)
The electrical installation stage in the process of building construction have risks to work safety and the operation of the results if the work is not following the General Electrical Installation Requirements (PUIL). This study aims to apply the development of Augmented Reality (AR) technology to provide convenience in the process of working on the electrical installation. Development of AR-based applications by utilizing android-based mobile phone devices which are now commonly owned by the public. The research was conducted by analyzing the electrical installation system in accordance with PUIL standards and its application in an easy-to-understand format, then processing electrical component data as input for 3D objects. Furthermore, the technical data of the building is used to produce AR applications that can be applied to the location of electrical installation work. The application that was built was successfully implemented on an Android-based cellular phone device. The rear camera is used to detect markers as triggers for the emergence of 3D objects in the form of electrical networks and electrical installation components. There are also info features and 3D object animations, as well as video calls as an alternative option for assistance if there are problems during electrical installation work.